2013
DOI: 10.1016/j.canlet.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activities of the targeted multi-tyrosine kinase inhibitor lenvatinib (E7080) against RET gene fusion-driven tumor models

Abstract: RET gene fusions are recurrent oncogenes identified in thyroid and lung carcinomas. Lenvatinib is a multi-tyrosine kinase inhibitor currently under evaluation in several clinical trials. Here we evaluated lenvatinib in RET gene fusion-driven preclinical models. In cellular assays, lenvatinib inhibited auto-phosphorylation of KIF5B-RET, CCDC6-RET, and NcoA4-RET. Lenvatinib suppressed the growth of CCDC6-RET human thyroid and lung cancer cell lines, and as well, suppressed anchorage-independent growth and tumori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
164
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(178 citation statements)
references
References 26 publications
3
164
0
6
Order By: Relevance
“…[20][21][22][23]) that has recently been approved for the treatment of radioiodine-refractory DTC (RR-DTC) on the basis of the results of the SELECT phase III trial (24). Preclinical and phase I evidence of antitumor efficacy in a variety of solid tumor types, including thyroid cancer (25)(26)(27)(28), prompted the initiation of a phase II trial in advanced, unresectable progressive MTC and RR-DTC, stratified by histology (29).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23]) that has recently been approved for the treatment of radioiodine-refractory DTC (RR-DTC) on the basis of the results of the SELECT phase III trial (24). Preclinical and phase I evidence of antitumor efficacy in a variety of solid tumor types, including thyroid cancer (25)(26)(27)(28), prompted the initiation of a phase II trial in advanced, unresectable progressive MTC and RR-DTC, stratified by histology (29).…”
Section: Introductionmentioning
confidence: 99%
“…Lenvatinib mesylate is a multityrosine kinase inhibitor of vascular endothelial growth factor receptors 1-3, platelet-derived growth factor receptor b, rearranged during transfection, and KIT (Matsui et al, 2008a,b;Okamoto et al, 2013). In a phase I study, lenvatinib was shown to have favorable PK properties, and its metabolic fate was investigated (Boss et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical evidence suggests that sorafenib blocks thyroid cancer growth through both antiproliferative and antiangiogenic mechanisms . Lenvatinib inhibits VEGFR1-3, fibroblast growth factor receptors 1-4, RET, c-KIT, and PDGFRβ [Matsui et al 2008;Okamoto et al 2013].…”
Section: Targeted Systemic Therapies For Rairefractory Thyroid Cancermentioning
confidence: 99%